Experimental Study on Application of Anhydrous Plaster Gypsum - Zhai, Hongxia; Yang, Lili; Zhang, Wulong; Ma, Xiaohui (Asian Journal of Chemistry, 2014)
With natural anhydrite (type II anhydrous gypsum) from Hanshan Country of Anhui Province as major raw materials, the preparation and application of anhydrous plaster gypsum are investigated. The physical properties and mechanical properties, ventilation property and respiratory capability of anhydrous plaster gypsum with different properties are detected by using the method of orthogonal test. The results show that compress strength reaches to 8.20 MPa after 14 days, the flexural strength reaches to 3.80 MPa after 14 days, the bonding strength reaches to 0.37 MPa after 7 days, initial setting time is 150 min, final setting time is 386 min. Micro-structure analysis indicates that the plaster is a kind of cellular material which has enormous internal specific surface area, favorable ventilation property and respiratory capability and coarse grain occluding the wall in a close way with no blister phenomenon. This material is an ideal inorganic fireproofing materials of free calcining, high performance price ratio and green nontoxic for interior wall painting.